Musical Characteristics of Tembang Dolanan Tamansiswa: A Quasi-Diatonic Approach in the Character Education Context - Heni Kusumawati; Ambar Fidianingsih; Ridwan Maulana; Esti Swatika Sari (Institut Seni Indonesia Yogyakarta, 2025)
Tembang dolanan, Javanese children's play songs performed in everyday play and school activities, remains a vital pedagogical repertoire within the Taman Siswa educational tradition in Yogyakarta. This article analyzes the musical structure of tembang dolanan used at SD Taman Muda Ibu Pawiyatan and formulates a quasi- diatonic harmonization model for classroom accompaniment. In this study, quasi- diatonic harmonization is deﬁned as an ethic, classroom-oriented translation layer: melodies derived primarily from sléndro and pélog pitch collections are supported by diatonic-referential sonorities while preserving their original pitch set and melodic contour. Salient melodic tones are therefore accommodated as added tones or suspensions, such as Iadd6, Iadd9, and sus11 sonorities, rather than treated as errors requiring melodic alteration. Using descriptive qualitative design, the study compiled ten songs from Tamansiswa song collections and recorded school performances; six songs that remain in routine teaching practice were then selected for focal analysis. The analysis examined form, meter, motivic processes, pitch and interval tendencies, and chord-melody relationships. The ﬁndings show a consistent structural proﬁle: predominantly unary forms, short repetitive phrases, stable simple meters, restricted pitch collections, frequent stepwise motion, and repeated tones. The article contributes an ethnomusicological account of a living school repertoire and offers a replicable intercultural framework for accompanying pentatonic-derived Javanese melodies in diatonic-oriented classroom environments without erasing their melodic identity